Exploring the impact of media use on wellbeing following a natural disaster - Raney, Arthur A.; Ai, Amy L.; Oliver, Mary Beth (Frontiers in Communication, 2022)
Media use can be beneficial in many ways, but little is known about how it might improve well-being outcomes following a traumatic natural disaster. Survivors (n = 491) of deadly Hurricane Michael, which struck the Florida (USA) coastline in 2018, completed an online survey, reporting indicators of posttraumatic growth (PTG) and stress (PTSS). A serial mediation model explored how hurricane-related stressors were related to both outcomes, as mediated by approach, avoidant, and support-seeking coping strategies and post-hurricane hedonic, eudaimonic, and self-transcendent media use as coping tools. Factors contributing to each type of post-hurricane media use were also explored. Results indicate that hurricane-related stressors were associated with PTG, serially mediated through approach coping strategies and self-transcendent media use, thus providing some of the first empirical evidence of the longer-term, beneficial well-being effects of media use on survivors of trauma. Additionally, hurricane-related stressors were associated with avoidant coping strategies, which were associated with increased eudaimonic media use. However, hedonic and eudaimonic media use were not associated with PTSS or PTG. Finally, factors known to be associated with media use were not predictive of post-hurricane media use, perhaps suggesting that media play a different role in survivors’ lives in the months following a traumatic event.